1999
DOI: 10.1016/s1386-4181(98)00008-1
|View full text |Cite
|
Sign up to set email alerts
|

Security bid/ask dynamics with discreteness and clustering: Simple strategies for modeling and estimation

Abstract: This paper proposes a dynamic model of bid and ask quotes that incorporates a stochastic cost of market-making, discreteness (restriction of quotes to a fixed grid) and clustering (the tendency of quotes to lie on "natural" multiples of the tick size). The Gibbs sampler provides a convenient vehicle for estimation. The model is estimated for daily and intradaily US Dollar/Deutschemark Reuters quotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Although bid/ask spread is an important factor in determining the overall degree of clustering, some of the prior empirical studies have shown that price clustering could also influence the bid/ask spread (ap Gwilym et al, 1998a;Hasbrouck, 1999). Hence, both the bid/ask spread and the degree of clustering could be determined simultaneously.…”
Section: Price Clustering Of Floor-traded and E-mini Index Futuresmentioning
confidence: 99%
“…Although bid/ask spread is an important factor in determining the overall degree of clustering, some of the prior empirical studies have shown that price clustering could also influence the bid/ask spread (ap Gwilym et al, 1998a;Hasbrouck, 1999). Hence, both the bid/ask spread and the degree of clustering could be determined simultaneously.…”
Section: Price Clustering Of Floor-traded and E-mini Index Futuresmentioning
confidence: 99%
“…Similar to the nonclustering noise, the biasing function b(·) can also depend on x, but the sequence of {b i (·)} is assumed to be independent given the value sequence {y i }. The random biasing function is similar to the clustering control variable proposed in Hasbrouck (1999).…”
Section: Construction Of Y From Xmentioning
confidence: 99%
“…Hence it is rather ironic that science, whether physical or social, often delivers just the opposite: parametric non-linear dynamics, driven by nonparametric non-Gaussian shocks. Hasbrouck (1999) Even in cases where theory does produce linear systems with parametric non-Gaussian disturbances, transformations can sometimes be used to achieve normality, allowing us to use traditional linear Gaussian methods instead of the more tedious Durbin±Koopman methods. Consider the stochastic volatility model, for example.…”
Section: J a Nelder (Imperial College Of Science Technology And Mementioning
confidence: 99%